AI, Robotics, and the Future of Waste Management: A Systematic Review of Advanced Collection and Sorting Systems - T. Rumaiza; Banu Priya M (International Journal of Robotics and Automation in Mechanics, 2025)
The rapid growth of cities and rise in population have made waste management a major concern that calls for innovative and efficient solutions. Conventional waste collecting techniques are dangerous, time-consuming, and frequently ineffective. The development of automated waste management systems powered by cutting-edge technology like robotics, deep learning, artificial intelligence (AI), and the Internet of Things (IoT) is examined in this study. Vision-based systems, convolutional neural networks (CNN) for garbage identification, IoT enabled smart bins, and solar-powered autonomous cars are just a few of the methods that are examined in a thorough literature analysis. The report emphasizes how well these technologies work to improve waste collection precision, cut down on human labor, and lessen pollution in the environment. However, limitations are noted, including restricted object differentiation, complex navigation, and scalability limitations. The study makes recommendations for future research topics, such as increasing energy economy, refining navigation algorithms, and increasing object identification accuracy. It is not only possible but also crucial to incorporate cutting-edge technologies into waste management systems in order to create cleaner and more intelligent urban settings.
Keywords: IoT in waste collection; Robotics; Waste management; artificial intelligence; collection and sorting of waste; robot navigation